MiR-218 suppresses gastric cancer cell cycle progression through the CDK6/Cyclin D1/E2F1 axis in a feedback loop. (10th September 2017) - Deng, Min; Zeng, Chao; Lu, Xihong; He, Xiusheng; Zhang, Ruixin; Qiu, Qinwei; Zheng, Guopei; Jia, Xiaoting; Liu, Hao; He, Zhimin
Abstract: Studies in several cancers have suggested that miR-218 has anti-tumor activities, but its function is yet to be elucidated. In this study, we investigated the regulation and function of miR-218 (miR-218-5p) in the cell cycle progression of gastric cancer (GC). We found that miR-218 could suppress proliferation of gastric cancer cells, induce cell cycle arrest at the G1 phase and inhibit tumor growth and metastasis in vivo. We also demonstrated that miR-218 specifically targeted the 3′-UTR regions of CDK6 and cyclin D1 and inhibited the expression of these molecules, which in turn repressed the pRb/E2F1 signaling pathway. Overexpression of CDK6 and Cyclin D1 reversed miR-218-mediated inhibition of pRB/E2F1 signaling and attenuated the miR-218-induced cell cycle arrest. More importantly, miR-218 expression was significantly reduced and inversely correlated with the levels of CDK6 and Cyclin D1 in gastric cancer tissues. Decreased miR-218 expression was also correlated with advanced clinical stage, lymph node metastasis, and poor prognosis in gastric cancer patients. Furthermore, we showed that miR-218 expression was directly activated by E2F1 through the transactivation of miR-218 host genes, SLIT2 and SLIT3, revealing a negative feedback regulation of miR-218 expression. Taken together, our results describe a regulatory loop miR-218-CDK6/CyclinD1-E2F1 whose disruption may contribute to cell cycle progression in gastric cancer and indicate the potential application of miR-218 in cancer therapy. Highlights: miR-218 suppresses gastric cancer cell cycle progression and tumor metastasis. miR-218 targets CDK6/Cyclin D1/E2F1 axis. E2F1 negative feedback regulates miR-218 expression. miR-218 is inversely correlated with CDK6 and Cyclin D1 expression in gastric cancer tissues. The reduced miR-218 levels are associated with malignant gastric cancer.